Surgically induced necrotizing scleritis after primary pterygium surgery with conjunctival autograft - Yamazoe K (Dove Medical Press, 2011)
Katsuya Yamazoe1,2, Seika Shimazaki-Den1, Isao Otaka3, Kazuki Hotta2, Jun Shimazaki1,4 1Department of Ophthalmology, Tokyo Dental College, Ichikawa, 2Department of Ophthalmology, Kameda Medical Center, Kamogawa, 3Yokohama Sotetsu Building Eye Center, Yokohama, 4Department of Ophthalmology, Keio University School of Medicine, Tokyo, Japan Background: Although pterygium excision with conjunctival autograft is a widely performed surgical procedure, surgically induced necrotizing scleritis (SINS) following such surgery is extremely rare. Methods: A 68-year-old man underwent nasal pterygium excision with conjunctival autograft uneventfully. On postoperative day 17, the conjunctival graft was avascular, with epithelial defect. Although topical steroid and antibacterial treatments were continued, the graft and sclera melted, with the ischemic sclera showing gradual thinning. The thinning area spread to the adjoining cornea, and active inflammation with epithelial defect was observed adjacent to the site of thinning. Results: Systemic and microbiological examination was noncontributory. The patient was suspected of having SINS, and administration of oral prednisolone was started. Although the necrotic area was reduced temporarily, medication was discontinued due to nausea, and the area of thinning increased. Conjunctival flap surgery was later performed, and the graft was well accepted. Conclusions: SINS must be considered in the differential diagnosis of patients with scleritis following pterygium surgery, especially if radiation or mitomycin C has not been used. Keywords: scleritis, pterygium, pterygium surgery, conjunctival autograft, SINS